Why the pervasive addiction myth is still believed - Hammersley, Richard; Reid, Marie (Addiction Research and Theory, 2025)
This paper characterises the myth of addiction and considers social mechanisms that may sustain this discourse about substance use problems in the face of counter-evidence. The myth is that substance use is typified by addiction, which is a dramatic, dangerous and chronic condition primarily caused by the biological effects of drugs. This myth is resilient and has been applied to different substances. Among the simple social mechanisms that may sustain the myth are that it provides a clear answer to drug problems and that it is socially-functional for a wide range of social groups (Davies, 1992. The Myth of Addiction. Reading, Harwood.). The literature on the nature and functions of myths and legends is briefly reviewed to show that the myth of addiction is of this form. As often with legends, the myth is partly an illustration of how not to behave. It also depicts issues of self-control that may be of central concern to western cultures. Loss of control through addiction is compared with loss of control through possession by deities or spirits, which is the most prevalent alternative source of 'loss of control', and the social mechanisms that surround both phenomena are described. It is also suggested that non-addiction can be an aspect of social identity. It is concluded that there is a need to reconsider substance use as normal behaviour with social causes, without perpetuating the unhelpful morality and unsuccessful solutions suggested by the myth.